Arnauld critique de Malebranche: le statut des idées - Glauser, Richard (My University, 1988)
ARNAULD'S THEORY OF REPRESENTATION (OPPOSING PICTORIAL AND LINGUISTIC REPRESENTATION TO IDEA-REPRESENTATION) EXPLAINS WHY HE HOLDS THAT MATERIAL OBJECTS MUST BE UNPERCEIVABLE BY THE MEANS OF MALEBRANCHEAN IDEAS. ARNAULD AVOIDS HIS CRUCIAL OBJECTION BEING TURNED AGAINST HIM. FOR HIM (1) (MATERIAL OBJECTS ARE PERCEIVED BY THE MEANS OF IDEAS) DOES NOT ENTAIL (2) (IDEAS ARE IMMEDIATE OBJECTS OF PERCEPTION). THE ROLE ARNAULD'S PERCEPTION-IDEA PLAYS IN THE (NONREFLEXIVE) PERCEIVING OF A MATERIAL OBJECT IS THAT OF THE ACT OF PERCEIVING WITH AN IMMANENT CONTENT. THUS, CONTRARY TO A MALEBRANCHEAN IDEA, IT IS NOT AN (IMMEDIATE) OBJECT OF A NONREFLEXIVE ACT OF PERCEIVING. IF (2) IS TRUE FOR ARNAULD, IT IS MERELY BECAUSE THE PERCEPTION-IDEA IS REFLEXIVELY PERCEIVED.
Keywords: Epistemology. Idea. Perception.